Developing and validating a novel in vitro smoke exposure model and investigating the innate immunological impact of cannabis smoke exposure on primary human bronchial epithelial cells - Chandiramohan, Abiram (My University, 2022)
Accessible in vitro models recapitulating the human airway that are amenable to study whole cannabis smoke exposure are needed for immunological and toxicological studies that inform public health policy as well as medicinal and recreational cannabis use. In the present study, we developed and validated a novel three-dimensional (3D)-printed in vitro exposure system (IVES) that can be directly applied to study the effect of cannabis smoke exposure on primary human bronchial epithelial cells (HBECs). Using commercially available design software and a 3D printer, we designed a four-chamber Transwell insert holder for exposures to whole smoke. COMSOL Multiphysics software was used to model gas distribution, concentration gradients, velocity profile, and shear stress within IVES. Following simulations, primary HBECs cultured at the air–liquid interface on Transwell inserts were exposed to whole cannabis smoke using a modified version of the Foltin puff procedure. Following 24 h, outcome measurements included cell morphology, epithelial barrier function, lactate dehydrogenase (LDH) levels, cytokine expression and gene expression. HBECs exposed to cannabis smoke using IVES showed changes in cell morphology and disruption of barrier function without significant cytotoxicity. Cannabis smoke elevated interleukin-1 (IL-1) family cytokines and elevated CYP1A1 and CYP1B1 expression relative to control. These findings validate IVES to have an effect in HBECs at a molecular level following cannabis smoke exposure. In addition, HBECs stimulated with a viral mimetic, Poly I:C, challenge following cannabis smoke exposure showed a suppression of key antiviral cytokines. The growing legalization of cannabis on a global scale must be paired with research related to potential health impacts on lung exposures. IVES represents an accessible, open-source, exposure system that can be used to model varying types of cannabis smoke exposures with HBECs grown under air–liquid interface culture conditions.
Keywords: Cannabis Smoke; in vitro model; Human Bronchial Epithelial Cells